Correction: Kanaan et al. Effect of Different Landscapes on Heat Load to Buildings. Land 2021, 10, 733 - Ahmed Kanaan; Bernd Leinauer; Matteo Serena; Elena Sevostianova; Burl Donaldson; Igor Sevostianov (Land, 2022)
In the original article [...]